Saturation and overcrowding of the emergency service of an urban hospital: Saturación y hacinamiento del servicio de emergencia de un hospital urbano - Taype-Huamaní, Waldo (2020)
Over-demand and overcrowding is a problem in the emergency department of our environment. Objective: to determine the characteristics of the demand for medical care at the emergency department of a tertiary social security hospital. Methodology: observational study at Rebagliati hospital, first quarter 2019. Sociodemographic, time and emergency indicators of the institutional statistical system, descriptive statistical statistics with IBM SPSS 24.00 were evaluated. Results: 51294 patient care between 14 and 102 years (median 60), 56.7% female sex, 18% recorded more than one visit in the quarter. Monday was the day of greatest demand and the schedule between 8 and 13 hours. Priority attention 3 and 4 corresponded to 60.8 and 20.8% of the total. The topics of medicine, relief and surgery performed 41, 22 and 20% of attentions respectively. In the shock trauma unit, 3% of attentions were performed. 13% attention was admitted to observation rooms. The most frequent diagnoses were respiratory failure, infections and strokes. 88% of admissions were made in common rooms with a stay between 4.4 and 7.0 days. 0.8% of those treated died, 0.7% performed surgery and 0.1% transferred to another hospital. Conclusion: the demand to the emergency department is mainly due to medical problems (priority 3 and 4), predominantly elderly and female patients. 13% of attention were admitted, with long stay, low mortality, very few transfers, high return rate and low supply of hospital beds.